2019
DOI: 10.1111/kykl.12197
|View full text |Cite
|
Sign up to set email alerts
|

Peer Effects on Weight Status, Dietary Behaviour and Physical Activity among Adolescents in Europe: Findings from the I.Family Study

Abstract: Summary This study uses survey data from the I.Family Study to investigate the association between adolescent and peer overweight in a sample of adolescents aged 12–16 from six European countries. We find clear evidence of peer effects on body mass index, waist circumference, and body fat, which are stronger among adolescents at the upper end of overweight distribution. We also provide evidence that both consumption of less healthy foods and time spent in leisure time physical activity and audio‐visual media a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 70 publications
1
13
0
1
Order By: Relevance
“…TV viewing, video games). 37 Consistent with earlier research, 5,6 our analyses indicate that there are annual increases in BMI across genders but that the predictors of the annual increase differ. Physical activity and substance use are not likely predictors of increasing BMI in females.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…TV viewing, video games). 37 Consistent with earlier research, 5,6 our analyses indicate that there are annual increases in BMI across genders but that the predictors of the annual increase differ. Physical activity and substance use are not likely predictors of increasing BMI in females.…”
Section: Discussionsupporting
confidence: 88%
“…39 Furthermore, peer effects are reportedly associated with differences in diet, exercise and BMI. 37,40 Recent findings from Europe also suggest that active experimenters likely have experimenter friends who tend to be We found that about one-quarter of youth transition to a "healthier" weight: 28.1% of youth with overweight/obesity in Wave 1 transitioned to a normal weight in Wave 2 and 27.3% of youth with overweight/ obesity in Wave 2 transitioned to a normal weight in Wave 3. Similar findings were reported from Spain, where 26% of youth classified as obese transitioned to overweight status.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Studies that have solely assessed the role of friends, generally revealed that similarities among friends are often found for foods typically consumed in peer contexts [25]. Given that these foods are usually unhealthy in nature (e.g., SSBs or snacks) [26,27] and are obtained from outside the home (e.g., at the school canteen, at the snack bar, or at the supermarket) [28], adolescents' intake is expected to be more similar to their best friends' food intake when considering unhealthy food obtained from outside the home. The few studies that have addressed the role of parents and friends simultaneously, showed positive associations between adolescents', parents', and friends' intake of SSBs [27] and found that adolescents' fruit and vegetables intake was positively related to their parents', but not to their friends' intake [29].…”
Section: Introductionmentioning
confidence: 99%
“…Family members are more alike in the intake of healthy In model 1e the age difference between the sibling is ≤2.7 years. In model 1f the age difference between siblings is > 2.7 years than unhealthy foods [3], while the opposite is true for friends [37], and friends tend to be particularly similar for snack and fast food consumption [13][14][15][16]38]. With increasing age, children might become more susceptible to peer pressures and peer social norms shaping their dietary and physical activity behavior.…”
Section: Discussionmentioning
confidence: 99%